2021
DOI: 10.3389/fmicb.2021.808593
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Unfolded Protein Response in Coronavirus Infection and Its Implications for Drug Design

Abstract: Coronavirus is an important pathogen with a wide spectrum of infection and potential threats to humans and animals. Its replication occurs in the cytoplasm and is closely related to the endoplasmic reticulum (ER). Studies reported that coronavirus infection causes ER stress, and cells simultaneously initiate unfolded protein response (UPR) to alleviate the disturbance of ER homeostasis. Activation of the three branches of UPR (PERK, IRE1, and ATF6) modulates various signaling pathways, such as innate immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Activation of the UPR is accompanied with changes of ER proteostasis, ER morphology and cargo proteins export, which suggest that ORF8 reshapes the ER to accommodate the requirement for virus replication and maturation. Indeed, accumulating evidences have shown that induction of the UPR may constitute a major aspect of coronavirus-host interaction [ 34 , 35 ]. Interestingly, EM images show that ORF8 promotes the ER membrane remodeling, which probably provide the major membrane source for virion assembly [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the UPR is accompanied with changes of ER proteostasis, ER morphology and cargo proteins export, which suggest that ORF8 reshapes the ER to accommodate the requirement for virus replication and maturation. Indeed, accumulating evidences have shown that induction of the UPR may constitute a major aspect of coronavirus-host interaction [ 34 , 35 ]. Interestingly, EM images show that ORF8 promotes the ER membrane remodeling, which probably provide the major membrane source for virion assembly [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been linked to the development of a wide spectrum of pathologies, including alcoholic- and non-alcoholic liver disease, various autoimmune and inflammatory disorders, and neurodegenerative diseases [ 59 ]. Several viruses have been shown to induce UPR, including SARS-CoV-2, HCV, and HBV [ 42 , 60 ]. The above-cited paper of Williams et al states that HDV antigens do not induce UPR, despite their data on the increased expression of a reporter under the control of an ERSE element that is one of the three key elements of UPR pathways [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the viral proteins S, ORF3a, ORF6, ORF7a, ORF8ab, and ORF8b of SARS-CoV are able to induce ER stress. Moreover, the use of pharmacological inhibitors of the UPR pathway regulates viral replication [ 41 ]. Upregulation of this pathway has been identified also in cells infected with SARS-CoV-2 and murine hepatitis virus (MHV), often used as a model for the Betacoronavirus genus.…”
Section: Introductionmentioning
confidence: 99%